Acute renal colic / renal stones – problematic common disease. Current knowledge on etiology, diagnosis and treatments - Bakalarczyk, Rafał; Rejmer, Adrian; Woś, Natalia; Rojek, Katarzyna; Bednarz, Lucjan; Wijas, Karolina; Bialic, Kinga; Szala-Czerwonka, Karolina; Bialic, Artur; Majewski, Paweł (Journal of Education, Health and Sport, 2023)
Introduction: An attack of renal colic as a result of kidney stones is one of the most common urological emergencies, with a wide spectrum of severity that generates high morbidity and high health costs. However, there is no single pharmacological treatment regimen for its acute phase. Renal colic is described as one of the worst types of pain, and effective analgesia in the shortest possible time is of paramount importance Aim of the study: Summary of current knowledge on the treatment of Acute renal colic / renal stones. The main purpose of our work is to review and summarize the various recommended options for the treatment of acute renal colic attack and prevention of recurrent urolithiasis depending on the type of stones and also to price the efficacy and safety profile of various drugs used in this ailment and to propose a practical treatment regimen. Material and methods: We conducted a literature search in PubMed using the terms "acute renal colic," "renal colic treatment," "anti-inflammatory drugs," "renal stones," and "fluid therapy." The most relevant clinical trials, meta-analyses and systematic reviews published from January 1, 2017 to January 1, 2022 in English and Spanish were reviewed. Results: In various studies reviewed, non-steroidal anti-inflammatory drugs (NSAIDs) show better pain control, with lower doses and fewer side effects than treatment with opioids. Complete cure in kidney stones is rare due to the frequent recurrence of the disease. Although acute attacks of renal colic are rare in the patients studied, many patients show improvement after taking nonsteroidal anti-inflammatory drugs. Opioids and fluid therapy are reserved for subsequent lines of treatment and also have proven benefits in relieving symptoms.